Reducing Postoperative Infections and Red Breast Syndrome in Patients With Acellular Dermal Matrix–Based Breast Reconstruction: The Relative Roles of Product Sterility and Lower Body Mass Index. (May 2015) - Lewis, Priya; Jewell, James; Mattison, Gennaya; Gupta, Subhas; Kim, Hahns
Abstract : Purpose: The use of human acellular dermal matrices (ADM) has become routinely used in implant-based breast surgery. Notwithstanding the many benefits for tissue support, the morbidity associated with its use includes seroma and infection, among other potential complications. Some patients experience a specific complication called red breast syndrome (RBS), which has been linked to ADM use, but its exact etiology remains elusive. In our institution, AlloDerm aseptic regenerative tissue matrix was recently replaced with a ready-to-use sterile version that undergoes terminal sterilization, eliminating the need for rehydration. We want to determine if this change in processing affected complications, including RBS. Methods: We conducted a retrospective chart review analyzing patients from January 1, 2011, to June 1, 2013, who underwent breast surgery with human ADM. Patients with aseptic AlloDerm were compared to patients with sterile AlloDerm. Data were analyzed using the Fisher exact test. Results: A total of 167 reconstructed breasts from 105 patients met inclusion criteria: 56% (n = 93) with aseptic ADM, 44% (n = 74) with sterile ADM. When comparing the two, patients had a decrease in overall necrosis, infection, seroma, and RBS with sterile ADM. However, the rates did not reach statistical significance. For example, the incidence of RBS decreased from 7.5% to 2.7% ( P = 0.301) and seroma decreased from 8.6% to 2.7% ( P = 0.188). The infection rate proved to be equivocal at 11.8% with aseptic ADM to 10.8% with sterile ADM ( P = 1.000). The only statistically significant change was a decrease in the total complication rate from 41.9% to 27.0% ( P = 0.046). The absolute risk reduction for total complications was 14.9% with a number-needed-to-treat of 7. Conclusion: According to our study, sterile AlloDerm has a clinically decreased incidence of complications compared to aseptic AlloDerm. Whereas RBS decreased, it was interesting to see that it was not eliminated altogether. This suggests that the etiology may be unrelated to ADM processing and warrants further investigation. Overall, the most notable difference was the statistically significant decrease in the total complication rate. Therefore, the change to sterile AlloDerm seems to be beneficial. Further benefit arises from ease of preparation in the operating room.